THE LIVING AND WORKING CONDITIONS OF SLOBOZHAN POTTER IN THE SECOND HALF OF THE 19TH - AT THE BEGINNING OF THE 20TH CENTURY. - Trubchaninov, Mykola (Sworld-Us Conference proceedings, 2022)
The study of pottery, especially at the current stage of the revival of Ukrainian national culture, is an urgent task of national historical science. The unstoppable internationalization of traditional household culture in Ukraine, the reduction in the nu